Analisis Komparatif Framing Pemberitaan Kasus Kekerasan Seksual dari Kapolres Ngada NTT di Media Merdeka.com dan Okezone.com - Yuni Dwi Maharani; Mayasari Mayasari; Oky Oxcygentri (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2026)
This study aims to analyze how the media present the news about the sexual violence case involving the Ngada Police Chief from East Nusa Tenggara (NTT) in the online media Merdeka.com and Okezone.com. This case has attracted public attention because the perpetrator is a law enforcement officer, making media coverage potentially influential in shaping public perception of the police institution and the issue of justice for the victim. This study uses a qualitative approach with framing analysis based on the model of Zhongdang Pan and Gerald M. Kosicki, which includes syntactic, script, thematic, and rhetorical structures. The data consists of six online news articles, three from Merdeka.com and three from Okezone.com, published in March 2025. The results show that Merdeka.com tends to highlight the victim's perspective through the use of emotional diction, the revelation of new facts, and narratives that are empathetic and advocative. In contrast, Okezone.com emphasizes the procedural and formal aspects, focusing on the legal process, the ethical trial, and official institutional statements, with minimal exploration of the victim's suffering. This difference indicates that news construction is heavily influenced by the editorial policies and journalistic orientation of each media outlet. This study recommends that media adopt a victim-centered perspective to raise social awareness and support the enforcement of justice in reporting sexual violence cases.